(untitled) - Jonathan Rosenberg (New York, 1996)
The book presents the basics of algebraic K-theory and its applications. Many topics from algebraic topology, homological algebra, and algebraic number theory are developed as needed. The final chapter gives a concise introduction to cyclic homology and its interrelationship with K-theory
Keywords: k-theory